Aesthetic Gynecology and Mental Health: What Does It Really Mean for Women? - Giuseppe Marano; Maria Benedetta Anesini; Greta Sfratta; Claudia d’Abate; Gianandrea Traversi; Sara Rossi; Francesco Maria Lisci; Caterina Brisi; Ida Paris; Roberto Pola; Eleonora Gaetani; Marianna Mazza (Cosmetics)
Body image, a complex interplay of perceptions, thoughts, and feelings about one’s physical appearance, has been a subject of extensive research. It is a dynamic construct that evolves throughout a woman’s lifespan, influenced by a multitude of biological, psychological, and sociocultural factors. From adolescence, marked by the onset of puberty and societal pressures to conform to specific beauty standards, to adulthood and the physical changes associated with aging, women’s body image undergoes significant transformations. Aging is a universal process that affects all organs, including the female genitalia. The vaginal tract undergoes significant atrophy due to declining estrogen levels, particularly during and after menopause. Aesthetic gynecology offers a range of procedures to address both functional and aesthetic concerns related to aging genitalia. Aesthetic gynecology, a burgeoning field within women’s health, provides various procedures aimed at enhancing genital appearance and function. It also helps balance the hormonal and anatomical changes that every woman experiences over time. The goal is to strengthen each patient’s intimate well-being and self-esteem, enabling them to experience intimacy peacefully. While often driven by concerns about physical attractiveness and sexual satisfaction, the psychological implications of these procedures are complex and multifaceted. It is crucial to recognize the interplay between psychological factors and the decision to undergo these procedures. Collaboration between surgeons and mental health professionals can ensure that candidates are psychologically prepared and have realistic expectations. By adopting a patient-centered approach and conducting rigorous research, healthcare providers can ensure that aesthetic gynecology is used as a tool for empowerment rather than exploitation. This article explores the intricate relationship between psychological well-being and aesthetic gynecology, examining how these procedures can impact body image, self-esteem, and overall quality of life.